2017
DOI: 10.4300/jgme-d-17-00035.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication With Surrogate Decision-Makers: A Pilot Initiative

Abstract: Residents' communication skills specific to surrogate decision-making benefit from focused interventions. Our pilot assessment of a workshop showed promise, and additionally demonstrated the feasibility of bringing OSCEs and simulated encounters into a busy clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Table 2 summarizes the 44 single-group, pre–post studies included in the review, 24–67 with 29 studies using a simulated evaluation and 16 using a clinical evaluation (1 study 31 reported on evaluations in both settings). Of the single-group, pre–post studies, 23 used outside observers to evaluate behavior change in a simulated setting, 24–26,28,30,31,33,36–40,42,47,51,54,60,62–67 with 20 reporting significant positive findings of skills change in at least one skill set or domain. Of the 11 studies using SP evaluations to evaluate behavior change in a simulated setting, 26,27,33,34,42,44,47–49,52,54 8 reported significant positive findings in at least one skill set or domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the 44 single-group, pre–post studies included in the review, 24–67 with 29 studies using a simulated evaluation and 16 using a clinical evaluation (1 study 31 reported on evaluations in both settings). Of the single-group, pre–post studies, 23 used outside observers to evaluate behavior change in a simulated setting, 24–26,28,30,31,33,36–40,42,47,51,54,60,62–67 with 20 reporting significant positive findings of skills change in at least one skill set or domain. Of the 11 studies using SP evaluations to evaluate behavior change in a simulated setting, 26,27,33,34,42,44,47–49,52,54 8 reported significant positive findings in at least one skill set or domain.…”
Section: Resultsmentioning
confidence: 99%
“…Of the single-group, pre-post studies, 23 used outside observers to evaluate behavior change in a simulated setting, [24][25][26]28,30,31,33,[36][37][38][39][40]42,47,51,54,60,[62][63][64][65][66][67] with 20 reporting significant positive findings of skills change in at least one skill set or domain. Of the 11 studies using SP evaluations to evaluate behavior change in a simulated setting, 26,27,33,34,42,44,[47][48][49]52,54 8 reported significant positive findings in at least one skill set or domain. Ten studies used outside observers to evaluate communication in a clinical setting, 29,31,43,45,46,53,56,57,59,61 with 5 reporting significant positive findings in at least one skill set or domain.…”
Section: Single-group Pre-post Studiesmentioning
confidence: 99%
“…19 Research suggests that EHR-specific empathic communication skills should be taught to practitioners, preferably via experiential learning opportunities, in which learners are observed in a supportive environment and provided direct feedback. 3,16,17,[19][20][21]23,33,34 Given that 46% of participants self-reported prior involvement in education or training on EHR-specific communication skills, this could have biased our results toward the null. An important question remains about whether EHR-specific behaviors truly correlate with better patient experience and, if so, by what means.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of OSCE workshops for practicing physicians in the literature are limited. There are few articles that identify the use of OSCEs in training surgical residents and emergency medicine residents, and there are two communication-specific OSCEs among primary care residents [ 7 , 8 , 11 , 17 ]. Among practicing physicians, there are several identified publications that report the use of OSCEs to enhance communication skills [ 10 , 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%